Trans women have worse cardiovascular biomarker profiles than cisgender men independent of hormone use and HIV serostatus. (1st November 2022) - Lake, Jordan E.; Wang, Ruibin; Barrett, Benjamin W.; Bowman, Emily; Hyatt, Ana N.; Debroy, Paula; Candelario, Jury; Teplin, Linda; Bodnar, Kaitlin; McKay, Heather; Plankey, Michael; Brown, Todd T.; et al.
Abstract : Background: Feminizing hormonal therapy (FHT) and HIV potentially alter cardiovascular disease (CVD) risk in transgender women (TW). Methods: TW were enrolled in Los Angeles, California and Houston, Texas and frequency-matched to Multicenter AIDS Cohort Study cisgender men (CM) on age, race, substance use, and abacavir use. Biomarkers of CVD risk and inflammation were assessed via ELISA. Wilcoxon rank sum and Fisher's exact tests compared TW and CM. Multivariable linear regression assessed factors associated with biomarker concentrations. Results: TW (HIV+ n  = 75, HIV− n  = 47) and CM (HIV+ n  = 40, HIV− n  = 40) had mean age 43-45 years; TW/CM were 90%/91% non-Hispanic Black, Hispanic, or Multiracial, 26%/53% obese, and 34%/24% current smokers; 67% of TW were on FHT. Among people with HIV (PWH), TW had higher median extracellular newly-identified receptor for advanced glycation end-products (EN-RAGE), lipoprotein-associated phospholipase A2 (LpPLA2), oxidized low-density lipoprotein (oxLDL), soluble tumor necrosis factor receptor type (sTNFR) I/II, interleukin (IL)-8 and plasminogen activator inhibitor (PAI)-1, but lower soluble CD14, von Willebrand factor (vWF) and endothelin (ET)-1 levels than CM. Findings were similar for participants without HIV (all P  < 0.05). In multivariable analysis, TW had higher EN-RAGE, IL-6, IL-8, P selectin, PAI-1, oxLDL and sTNFRI/II concentrations, and lower vWF, independent of HIV serostatus and current FHT use. Both being a TW and a PWH were associated with lower ET-1. Conclusions: Compared to matched cisgender men, trans women have altered profiles of biomarkers associated with systemic inflammation and CVD. Further work is needed to decipher the contributions of FHT to CVD risk in TW with HIV.